A Meta-Analysis-Based Study of the Factors Influencing Students' Engagement in Classroom Learning - Jiaxin, Feng (International Conference on Fundamental and Applied Research (I-CFAR), 2026)
In response to inconsistent findings in existing research on the factors influencing students’ classroom learning engagement, this study aims to systematically synthesize and re-examine empirical evidence in this field through a meta-analysis to derive more generalizable conclusions. Method/Process: Using a meta-analytic approach that integrates both qualitative and quantitative methods, 43 high-quality empirical studies that met the inclusion criteria were rigorously screened from international and domestic sources. Comprehensive Meta-Analysis (CMA) software was employed to aggregate reported effect sizes (correlation coefficients), followed by heterogeneity testing, publication bias assessment, and moderator analysis. Results/Conclusion: The analysis identified 13 factors that significantly influence student classroom engagement. Effect size estimates indicated that teacher–student relationships, students’ thinking skills, emotional factors, and teacher behaviors showed moderate correlations with engagement, marking them as key determinants. Moderator analysis further revealed that educational stage (basic education vs. higher education) significantly moderated the effects of three factors, personality traits, thinking skills, and learning background, with stronger correlations for personality traits and thinking skills observed at the basic education level. Innovation/Value: By quantifying the influence of multiple factors and elucidating the moderating role of educational stage, this study clarifies heterogeneity in prior findings and provides a robust theoretical foundation and practical guidance for developing targeted strategies to enhance student engagement across different educational phases.